Progressive lentivirus infection induces natural killer cell receptor-expressing B cells in the gastrointestinal tract. (31st July 2018) - Manickam, Cordelia; Nwanze, Chiadika; Ram, Daniel R.; Shah, Spandan V.; Smith, Scott; Jones, Rhianna; Hueber, Brady; Kroll, Kyle; Varner, Valerie; Goepfert, Paul; Jost, Stephanie; Reeves, R. Keith
Abstract : Objective: Recently, a seemingly novel innate immune cell subset bearing features of natural killer and B cells was identified in mice. So-called NKB cells appear as first responders to infections, but whether this cell population is truly novel or is in fact a subpopulation of B cells and exists in higher primates remains unclear. The objective of this study was to identify NKB cells in primates and study the impact of HIV/SIV infections. Design and Methods: NKB cells were quantified in both naive and lentivirus infected rhesus macaques and humans by excluding lineage markers (CD3, CD127) and positive Boolean gating for CD20, NKG2A/C and/or NKp46. Additional phenotypic measures were conducted by RNA-probe and traditional flow cytometry. Results: Circulating cytotoxic NKB cells were found at similar frequencies in humans and rhesus macaques (range, 0.01−0.2% of total lymphocytes). NKB cells were notably enriched in spleen (median, 0.4% of lymphocytes), but were otherwise systemically distributed in tonsil, lymph nodes, colon, and jejunum. Expression of immunoglobulin was highly variable, but heavily favoured IgM and IgA rather than IgG. Interestingly, NKB cell frequencies expanded in PBMC and colon during SIV infection, as did IgG expression, but were generally unaltered in HIV-infected humans. Conclusion: These results suggest a cell type expressing both natural killer and B-cell features exists in rhesus macaques and humans and are perturbed by HIV/SIV infection. The full functional niche remains unknown, but the unique phenotype and systemic distribution could make NKB cells unique targets for immunotherapeutics or vaccine strategies. Abstract : Supplemental Digital Content is available in the text